Competency-Based Human Resource Management (CBHRM) is a new model of performance management which synchronized the business strategy and the human resources strategy in order to reach the goal of an organization. It is also one of the concepts to build the core competencies of a company to get their competitive advantages. ThiS research analyzed the business strategy and the arrangement of CBHRM action plan in PT XYZ. Two methods were use to reach the goal of the research. The methods are SWOT a - Iis Diatin; Suharno .; Evita Fathia Luthfina (Buletin Ekonomi Perikanan, 2005)
Competency-Based Human Resource Management (CBHRM) is a new model of performance management which synchronized the business strategy and the human resources strategy in order to reach the goal of an organization. It is also one of the concepts to build the core competencies of a company to get their competitive advantages. ThiS research analyzed the business strategy and the arrangement of CBHRM action plan in PT XYZ. Two methods were use to reach the goal of the research. The methods are SWOT analysis and Performance Improvement Planning (PIP). The result shows that PT XYZ could implement three alternative sfrategies as their grand strategies. The grand strategies are: (1) implementing the ISO system along with training and development, especially the training that related to the ISO system, for their employees, (2) pursuing continuous improvement and also (3) expanding their market share. Based on the analysis by using PIP method, PT XYZ has ten fastics to build their employees competencies in adopting the concepts of CBHRM. Several of the tactics are: (1) socializing vision and mission of the company, (2) arranging training and development, (3) tightening the supervision of the prosses and products.